Prolonged standing at work and hospitalisation due to varicose veins: a 12 year prospective study of the Danish population - Tuchsen, F (BMJ Group, 2005)
Background: Recent studies suggest that prolonged standing at work is associated with the development of diseases of varicose veins (VV). Aims: To assess the risk of hospitalisation due to VV in the lower extremities prospectively in workers standing or walking at least 75% of their time at work. Methods: A representative random sample of 9653 working age adults was drawn from the Central Population Register of Denmark in 1991. Of these, 8664 accepted to be interviewed by telephone (response rate 90%). Respondents (2939 men and 2708 women) were 20–59 years old and employed in 1990. Risk ratios for VV were estimated by log-linear Poisson regression models separately for men and women with adjustment for smoking status, body mass index (BMI), heavy lifting, and, for females only, number of children at baseline. Results: During 12 years of follow up, 40 hospitalisations due to VV were observed among the men and 71 among the women. For employees with jobs that require prolonged standing or walking compared to all other employees, the relative risk was 1.75 (95% CI 0.92 to 3.34) for men and 1.82 (95% CI 1.12 to 2.95) for women. The pooled estimate of the relative risk was 1.78 (95% CI 1.19 to 2.68). The aetiological fraction of prolonged standing or walking at work was estimated as 22.5% for men and 22.6% for women. Conclusions: This prospective study confirms that prolonged standing at work constitutes an excess risk of hospital treatment due to varicose veins and accounts for more than one fifth of all cases of working age.